2010
DOI: 10.1016/j.otsr.2010.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Is combining massive bone allograft with free vascularized fibular flap the children's reconstruction answer to lower limb defects following bone tumour resection?

Abstract: Level IV. Retrospective therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The incidence of delayed union was less than 1%, comparatively lower than reported incidences ranging from 4% to 33.3% [7, 8, 20-23, 26, 29]. Partial weightbearing was allowed by 2.6 ± 1 months and full weightbearing ambulation was permitted by 12 ± 5 months, similar to those reported for 2 months [31] and 13 months [20][21][22][23]26] on average, respectively. The low incidence of delayed union and subsequent deformities between our two groups we believe is attributable to central placement of the vascularized fibula graft in the massive bone allograft shell followed by adequate and stable osteosynthesis [7,9,34].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The incidence of delayed union was less than 1%, comparatively lower than reported incidences ranging from 4% to 33.3% [7, 8, 20-23, 26, 29]. Partial weightbearing was allowed by 2.6 ± 1 months and full weightbearing ambulation was permitted by 12 ± 5 months, similar to those reported for 2 months [31] and 13 months [20][21][22][23]26] on average, respectively. The low incidence of delayed union and subsequent deformities between our two groups we believe is attributable to central placement of the vascularized fibula graft in the massive bone allograft shell followed by adequate and stable osteosynthesis [7,9,34].…”
Section: Discussionsupporting
confidence: 69%
“…Several studies involving middle and distal tibia reconstructions with pedicled fibula grafts alone have shown good results with the advantage of being less expensive, a technically easier procedure, associated with minimal complications, and with a predictable long-term clinical outcome [2, 11-13, 19, 30]. Other studies involving vascularized fibula and massive bone allograft constructs have shown similar advantages, focusing either on only free vascularized fibula [4,7,10,[21][22][23]31] or pedicled vascularized fibula with massive bone allografts [9,29]. However, to our knowledge, there are no published studies on indications or comparisons for free versus pedicled vascularized fibula grafts supplementing massive bone allografts in tibia diaphyseal sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft reconstructions are associated with complications such as fracture, nonunion, and infection [15,24]. The transfer of vascularized bone from the fibula, with or without growth plate [19], is widely used to bridge large defects; however, donor-site morbidity has been reported to occur in as much as 19% of patients [27]. The relatively poor initial stability in adults owing to the thinness of the fibula has led some surgeons to resort to surrounding the vascularized fibula graft in an allograft shell [19].…”
Section: Discussionmentioning
confidence: 99%
“…The transfer of vascularized bone from the fibula, with or without growth plate [19], is widely used to bridge large defects; however, donor-site morbidity has been reported to occur in as much as 19% of patients [27]. The relatively poor initial stability in adults owing to the thinness of the fibula has led some surgeons to resort to surrounding the vascularized fibula graft in an allograft shell [19]. Vascularized bone transfer is more suitable for young children in whom initial stability is better, even though some with diaphyseal reconstruction also need a growth-plate transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation